Phytochemicals - Bioactivity of Avicennia marina Leaves Extract, and Its Application in Food Products: A Brief Literature Review - Jatmiko Eko Witoyo; Panggulu Ahmad Ramadhani Utoro (Department of Agricultural Engineering, Syiah Kuala University, 2023)
Abstract. Avicennia marina (A. marina) is a tropical and non-tropical biodiversity that grows along the coast worldwide, including Indonesia. A. marina, known as the